Analisis Peningkatan Kemampuan Calistung Melalui Bimbingan Belajar - Syafriza, Azizatul Alif; Junanto, Muhammad Wachid; Fadilah, Erizal Afif; Yanuar, Doni; Hanif, Muhammad Naufal; Zahroh, Fatimatu; Munawaroh, Isti; Azzahro, Yuni Sulistya; Mufarida, Nisa Arifatul; Syamsudin, Muhammad (Universitas Muhammadiyah Magelang, 2023)
Analytical research on improving calistung abilities was carried out because of complaints that emerged from the school that there were still many students in class VI who were still weak in calistung. This research was conducted with the aim of describing the implementation of tutoring activities to determine learning outcomes and improve the calistung abilities of class VI students at SD NU Pemanahan. This research uses a qualitative descriptive research method. With a population of 10 students in class VI of SD NU Pemanahan. Data collection techniques in this research used interviews, observation and documentation. Interviews were conducted with class VI teacher Mrs. I, to determine the development of students' calistung abilities when learning in class. Meanwhile, observations were made during the guidance process. Documentation in the form of photos, videos and student evaluation results over a period of time after guidance. The data analysis technique is carried out through three stages, namely data reduction, data presentation, and drawing conclusions. In implementing the guidance process, students are divided into 3 categories, namely less fluent in calistung, less fluent in reading and writing, and the third less fluent in arithmetic. Grouping is done to make it easier to provide guidance. After the end of the guidance process, a test of the abilities of each group was carried out and the results showed that they had improved. From the results of interviews with teachers, there was a significant improvement in the class during the learning process after the guidance process was carried out. So there was an increase in calistung ability in students who were given tutoring treatment.